Framing digital future : Selective formalization and legitimation of ridehailing platforms in Estonia - Lanamäki, Arto; Tuvikene, Tauri (Elsevier, 2021)
The contribution of the paper to the geographical literatures on informalities is to expand the work on transport informalities from transport system reforms and professionalization of informal provisions such as minibus services or taxi provisions to ridehailing, including explicit discursive framings through which formalization operates. Ridehailing platforms have entered various cities around the world extra-legally, forcing public authorities to deal with them. While there is an emerging literature discussing various aspects of ridehailing and platform economies, the literature to date has not analyzed what kinds of discursive frames facilitate the legitimation of these businesses. Analyzing legitimation through frame analysis highlights the affective forcefulness of future visions configured around technology-oriented regulation, employment provision and digitalization. The article argues that the state acceptance of sharing platforms, together with the introduction of the legal framing for them, particularly gains strength from the frame promising digital future. In such policy-framing processes, sharing platforms’ extra-legal entry into the market as a form of “elite informality” becomes accepted instead of being considered illegal. This paper analyzes verbatim reports of debates regarding ridehailing legalization held at the Estonian parliament (Riigikogu) in April and September 2016. These verbatim reports represent a key event and arguably the most public part of the trajectory from Uber entering Estonia extra-legally in May 2015 to Estonia introducing the “Uber law” legalizing ridehailing in 2017.
Keywords: Policy framing; Legitimation; Informality; Uber; Bolt; ridesharing; fi=Viestintätieteet|en=Communication Studies|